Nurse champions as street-level bureaucrats: Factors which facilitate innovation, policy making, and reconstruction - Sperling, Daniel; Shadmi, Efrat; Drach-Zahavy, Anat; Luz, Shirly (Frontiers in Psychology, 2022)
Background: Nurse champions are front-line practitioners who implement innovation and reconstruct policy. Purpose: To understand through a network theory lens the factors that facilitate nurse champions' engagement with radical projects, representing their actions as street-level bureaucrats (SLBs). Method: A personal-network survey was employed. Ninety-one nurse champions from three tertiary medical centers in Israel participated. Findings: Given high network density, high levels of advice play a role in achieving high radicalness than lower levels advice. High network density is also related to higher radicalness when networks have high role diversity. Discussion: Understood under the SLB framework, nurse champions best promote adoption of innovation and offer radical changes in their organizations through professional advice given by colleagues in their field network. Healthcare organizations should establish the structure and spread the values for the development of dense and heterogeneous professional networks to realize organizations' goals and nurses' responsibility to their professional employees, patients and society.